Najnowsze sondowania wybranych jezior Pojezierza Wielkopolsko-Kujawskiego - Choiński, Adam; Ptak, Mariusz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
The article presents the results of bathymeter measurements of formerly untested lakes of the Wielkopolskie and Kujawskie Lake districts with areas exceeding 50 ha. It has been established that the volume of water in the six lakes amounts to 22,980 [thou. cubic m.] while their total area amounts to 267.9 [ha]. The research results have enriched the available data on the bathymetric parameters of the region in question. At present, in the Wielkopolskie and Kujawskie Lake districts only one lake (with an area exceeding 50 ha) out of 193 has not been provided with detailed information about the hypsometry of the lake’s bottom. Bathymetric measurements conducted in various parts of Poland (both new and those updating the existing bathymetric plans) should be deemed valuable and necessary. These measurements provide a new source of information which serves, among other things, to evaluate the recent direction and rate of evolution of lake basins and the changes to the water resources stored in lake basins.
Keywords: lakes; morphometry; bathymetry; water resources